The Advantage in a Dustheap-rag: (Paṁsukūlānisaṁsa) - Masefield, †Peter; Filliozat, Jacqueline; Revire, Nicolas (The Journal of the Siam Society, 2024)
This study begins by providing a brief overview of the Thai Buddhist tradition of bangsukun, in which discarded rag robes (paṁsukūla) are offered to monks as symbols of life’s impermanence (anicca) and to share merit (puñña). We then present a fresh new edition and English translation of the Paṁsukūlānisaṁsa, a rare Pali text composed in Thailand that details the spiritual benefits of offering dustheap-rag robes to buddhas and monks. Rooted in early Buddhist ascetic practices, the text adapts canonical themes to local contexts, highlighting the transformative power of simple offerings and underscoring the central role of merit-making in Buddhist society.